Analisis Minat Belajar pada Pembelajaran Matematika - Rizki Nurhana Friantini; Rahmat Winata (STKIP Singkawang, 2019)
The purpose of this study was to analyze and describe the students’ learning interest of class X IIS 1 Jelimpo Senior High School in the academic year of 2018/2019 in Landak Regency. This study was descriptive qualitative. The subject of this study was the students of X IIS consisted of two classes. The sample of this study was 76 students who were selected using saturated sampling technique. The technique in collecting data was using questionnaire. The result shows that the students’ percentage average score was 58%. So it can be concluded that most students are interested in learning mathematic. Based on gender, male students reach the average percentage of 55% and female students reach 62%. Thus, most of them have learning interest of mathematic. If it is compared, the percentage average of female students’ interest in learning mathematic is higher than male students (62% > 55%). In short, the female students’ learning interest is higher than male students’ in mathematic subject for class X IIS 1 Jelimpo Senior High School.